ANALISIS FUNGSI MANAJEMEN PUSKESMAS PADANGSARI KECAMATAN BANYUMANIK KOTA SEMARANG - Priyandani Akbar; Endang Larasati; Susi Sulandari (Journal of Public Policy and Management Review, 2015)
Various problems such as lack of competent human resources areas and a lack of community participation in the management of PHC Padangsari follow Semarang into the background of this research. This study aims to determine how the analysis of the health center management functions Padangsari in Semarang and identify factors driving and inhibiting factors in the health center management functions Padangsari in Semarang. This study uses descriptive qualitative research methods. The subjects in this study consists of three (3) key informants.The results showed that the health center management functions Padangsari been going well, but in the Human Resources sector is still lacking to fill the existing field. Most of these employees are still concurrently or have two different responsibilities, this indicates the duties and functions of employees to be heavy in the implementation cause less focus employees in performing their obligations to be not optimalize results. Then, community participation is still low the limiting factor in the management of health centers Padangsari. Elements of such participation is absolutely necessary for the success of the programs implemented by PHC ( Public Health Center ) Padangsari. The community is only as passive participators in some programs implemented in the management of health centers Padangsari which is the National Health Development Program as an attitude or lifestyle clean environment.Based on these conclusions, the researchers recommend to Padangsari health centers to provide training - training to employees in accordance with the competencies required in the implementation of management functions. PHC Padangsari need to increase the active participation of the community to implement the National Health Development Program as an attitude or a healthy lifestyle environment.